2022
DOI: 10.1007/s11192-022-04310-z
|View full text |Cite
|
Sign up to set email alerts
|

Toward greater consistency and validity in measuring interdisciplinarity: a systematic and conceptual evaluation

Abstract: While interdisciplinary research (IDR) has attracted much attention, this has not yet resulted in a coherent body of knowledge of interdisciplinarity. One of the impediments is a lack of consensus on its conceptualization and measurement. Some of the proposed measures have shown to misalign empirically, meaning that conclusions about IDR can differ across measures. To clarify this disagreement conceptually, and to stimulate better coherence in measurement, this paper starts with a review of the IDR definitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Beyond the Rao-Stirling Diversity and Generalised Diversity there are alternative measures (Wang and Schneider, 2020;Zwanenburg et al, 2022); most of these can be still related to or derived as special cases of the Shannon formulation of the concept of Entropy, that is:…”
Section: Alternatives To Diversity: Generalised Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the Rao-Stirling Diversity and Generalised Diversity there are alternative measures (Wang and Schneider, 2020;Zwanenburg et al, 2022); most of these can be still related to or derived as special cases of the Shannon formulation of the concept of Entropy, that is:…”
Section: Alternatives To Diversity: Generalised Entropymentioning
confidence: 99%
“…Many valid measures of IDR can be found in the literature. Methodological reviews as Molas-Gallart et al (2014), Wang and Schneider (2020), and Zwanenburg et al (2022) actually found dozens of mathematical formula for the same dimensions, to the point that these studies ended up questioning the validity of so many measures in absence of numerical convergence in results. In addition, consider that in order to determine the uncertainty of results exclusively due to the variation in operational definitions, the authors fixed the taxonomy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies on the measurement of IDR diversity have also focused on synthetical indicators that can integrate the three components (Leydesdorff et al, 2019; Stirling, 2007; Zhang et al, 2016). Zwanenburg et al (2022) constructed criteria for IDR measurement, and evaluated 21 measures of IDR, finding that these measures that capture all aspects of diversity could gauge IDR more effectively. Hitherto, many studies on IDR diversity have taken each dimension and the synthesis of diversity into account.…”
Section: Literature Reviewmentioning
confidence: 99%